PROCALCITONIN AS ANTIMICROBIAL MANAGEMENT TOOL IN COVID-19 PATIENTS - Lenardt, Maria Helena; Cechinel, Clovis; Rodrigues, João Alberto Martins; Binotto, Maria Angélica; Zanata, Isabel de Lima; Kraus, Rosane; Marques, Daiane Maria da Silva (Cogitare Enfermagem, 2023)
Objective: to investigate the relationship between procalcitonin in the differential diagnosis of bacterial coinfection in COVID-19 patients. Method: a cross-sectional retrospective study conducted between February and March 2021 in the Intensive Care Unit of a public hospital from southern Brazil by filling in a form. Descriptive statistical analyses were performed, as well as of association between variables. Results: of the 231 patients, 28.14% presented infection (63.20% in the lungs), 25% had bacteria isolated, 77.49% used antimicrobials and, in 14.72% of the cases, procalcitonin > 2 ng/mL. There was a significant association between antimicrobial use and infection (p=0.001), isolation of bacteria (p<0.001), topography of the infection (p<0.001) and procalcitonin values (p<0.001). Procalcitonin use showed an association with bacterial infection (p<0.001), isolation of bacteria (p<0.001), antimicrobial use (p=0.001) and death (p<0.001). Conclusion: procalcitonin can reduce empirical antimicrobial use and stimulate detection and identification of pathogens, taking into account the clinical and epidemiological data.